Limited şirkette oy hakkı ve kullanılması - Sevencan, Buşra (My University, 2019)
“Limited Şirkette Oy Hakkı ve Kullanılması” başlıklı tezimizin amacı, uygulamada geniş yer tutan limited şirketlerde, pay sahibinin en önemli haklarından biri olan oy hakkının Türk Ticaret Kanunu’nun hükümleri, doktrin ve yargı kararları çerçevesinde incelenmesidir.6102 sayılı Türk Ticaret Kanunu ile limited şirketlerle ilgili olarak anonim şirketler hükümlerine pek çok noktada atıf yapılmıştır. Ancak limited şirkette oy hakkının, niteliği itibariyle ayrıca düzenlenmesi ve çoğu durumda anonim şirketten ayrılan yönleri olduğundan yapılan atıflar uygulamadaki ihtiyaçları karşılamakta yetersiz kalmaktadır. Bu nedenle çalışmada, pay sahibinin oy hakkı limited şirket hükümleri doğrultusunda incelenmiş, gerektiğinde anonim şirket hükümleri ile karşılaştırılmıştır. Bu kapsamda çalışmamızda oy hakkının tanımı, hukuki niteliği, özellikleri oy hakkının kazanılması, oyun hesaplanması, oyda imtiyaz, üstün oy, oy hakkının kullanılması ve oy hakkının sınırları konuları ele alınmıştır.

The purpose of this thesis is to examine the voting rights, which is one of the most important rights of the shareholders, in limited liability companies which have a wide application in practice, within the framework of the provisions of Turkish Commercial Code, doctrine and judicial decisions. The Turkish Commercial Code numbered 6102 refers to the provisions of joint stock companies at many points in the limited liability company. However, since the voting right in a limited liability company is regulated separately and, in many cases, is separated from the joint stock company, citations are insufficient to meet the needs in practice. Therefore, the voting rights of the shareholders were examined in accordance with the provisions of the limited liability company and compared with the provisions of joint stock companies when necessary. In this contex, the definition of the voting right, its legal characteristics, its characteristics, acquisition of the voting right, the calculation of the vote, the privilege in the vote, the superior vote, using of the voting right and the limits of the voting right were examined.
Keywords: Civil law; Commercial law; Limited liability company; Limited şirket; Medeni hukuk; oy hakkı; oy hakkının kullanılması; Ticaret hukuku; using of voting right; voting right